ANALISIS FAKTOR DETERMINAN YANG MEMPENGARUHI PEMAKAIAN METODE JIT (STUDI KASUS UD. PUSAKA BAKTI) - ARAFAH, SANTI; TANJUNG, YAHYA (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
The system is an indispensable procedure in a company engaged in the service trade, as well as in manufacturing in order to run a business activity. One of the companies that have to apply and replace the system inventory items that are traditional systems of inventory items that bermetode JIT (Just in Time) is a UD. Pusaka Bakti. This research aims to find out how much influence the cost of production, goods production, quality of goods production and employee performance against the use of methods JIT. Analytical techniques used in the form of multiple linear regression analysis technique. The results of the analysis of research conducted with alpha 5% shows that simultaneously between the variable costs of production, goods production, quality of goods production and employee performance affects usage of methods JIT. However, partially variable production costs and quality of goods production does not affect the use of methods JIT. While the variable production costs and employee performance positive and significant effect against the use of methods JIT.Key words: Cost of Production, Goods Production, Quality of Goods Production, Employee Performance and Method JIT